Pengaruh Hasil Belajar Matematika Terhadap Kecerdasan Emosional Siswa Kelas IX SMP Negeri 13 Jember - Septiana, Sheila Wahyu; Sunardi, Sunardi; Oktavianingtyas, Ervin (Kadikma, 2017)
Abstract This research describse the influence of learning mathematics of emotional intelligence of students of class IX SMP Negeri 13 Jember. The sample in this study were 59 students and the instruments used were test and questionnaire. This research is done by giving math test to get the data of learning result, then to measure the emotional intelligence of the students are asked to fill the questionnaire of emotional intelligence. His emotional types include sadness, joy and happiness. Before the instrument is tested. Analysis of validation data about math test and questionnaire obtained value Va = 2,68 and based on the category of validity level of the instrument. Based on the results of the analysis of the lowest value of 22, the value of the questionnaire included in the excellent category 12 students, good category 46 students and the category is good enough 1 student. From the result of data analysis, it can be concluded that there is influence of learning result to student’s emotional intelligence. The percentage of influence of learning outcomes on emotional intelligence is 9%. Results of mathematics learning. Keywords : Emotional intelligence, mathematics learning outcomes